Crystal growth of alpha-rhombohedral boron - Gao, Wei (Kansas State University, 2010)
Pure boron exists in two main polymorphs, the common β-rhombohedral boron and the relatively rare α-rhombohedral boron. α-rhombohedral boron (α-B) possesses several extraordinary properties: self-healing from radiation damage and a high hole mobility. In addition, the [superscript]10B isotope has a large thermal neutron capture cross section. Such properties make it an excellent candidate for novel electronic device, such as direct energy conversion devices (alphacells and betacells) and neutron detectors. However, research on the properties and applications of α-B has been limited due to the difficulty to produce high quality α-B crystals of significant size. The preparation of α-rhombohedral boron is challenging for several reasons: first, α-rhombohedral boron has a low thermodynamic stability; it is only stable below 1100°C, at higher temperature β-rhombohedral boron is the stable polymorph. In addition, at elevated temperatures, boron is highly reactive, which make it is difficult to produce pure boron crystals. The primary goal of this research was to produce high quality α-B crystals of significant size. The main focus of this study was to explore the feasibility of producing α-B from a copper flux. Copper is a promising solvent for α-B crystal growth: the eutectic temperature of copper-boron is low, 996°C, and the phase diagram of copper-boron is relatively simple, and there are not many intermediate boride-copper compounds. In addition, copper is easily removed from crystals by etching with concentrated nitric acid. Last but not least, copper is less expensive than other metal solvents such as platinum. Boron crystal growth from a platinum solvent and vapor-liquid-solid growth by chemical vapor deposition were also performed for comparison. A series of crystals were grown over a range of initial boron concentrations (9.9 to 27.7 mole %) and cooling rates. Small irregular-shaped black crystals (>100μm) and well-faceted red crystals in various shapes, as large as 500 microns were produced. The crystals were characterized by optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, x-ray diffraction analysis, and Raman spectroscopy. The correlation between experiment results and experimental parameters (source materials, the purity of growth atmosphere, and crucible materials, etc.) are reported. Suggestions about further investigation for α-B crystal growth are proposed.
Keywords: Alpha-rhombohedral Boron; Icosahedral boron-rich solids; Chemical engineering; Solution growth method; Semiconductor; Neutron detector; Engineering, Chemical (0542)